STRUCTURE-BASED VIRTUAL SCREENING, MOLECULAR DOCKING, AND DYNAMICS SIMULATION APPROACHES FOR IDENTIFICATION OF INHIBITORS OF HELICOBACTER PYLORI MQNB - ANANDAMURTHY, ARTHIKASREE; GARISETTI, VASAVI; VARUGHESE, ROSLIN ELSA; GAYATHRI DASARARAJU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Helicobacter pylori is the major cause of duodenal ulcers and gastric cancer. Menaquinone is essential for the respiration and survival of H. pylori. Identification of compounds that have good binding affinity at the active site of MqnB will be the promising approach against H. pylori. This study aims to identify the natural lead compounds against MqnB enzymes in H. pylori through in silico methods. Methods: As the three-dimensional structure of H. pylori MqnB is not available, we have modeled the three-dimensional structure followed by identification of the active site. The binding of the compounds from the COlleCtion of Open NatUral prodUcTs database was screened against MqnB, and dynamics simulation studies were carried out for the top three lead compounds. Results: The predicted model of MqnB was subjected to a molecular dynamics (MD) simulation study to obtain the dynamic behavior of MqnB. The best representative model was validated and further used for structure-based virtual screening. Based on the docking results, three lead compounds were chosen among the top hits and subjected to 200 ns MD simulation. The results highlight the dynamic nature of MqnB in complex with the lead compounds and favorable binding interactions are comparable with the substrate. All the compounds showed promising interactions with MqnB during MD simulations. Conclusion: Identified lead compounds show good binding potential and also maintain interactions with amino acid residues at the active site of MqnB enzyme. These compounds could be further explored in the drug discovery process against H. pylori.